Composite circulation index of weather extremes (the example for Poland) - Zbigniew Ustrnul; Agnieszka Wypych; Danuta Czekierda (Meteorologische Zeitschrift, 2013)
The paper describes the implementation of a composite circulation index of weather extremes (CIE). The new index informs about the synoptic conditions favoring the occurrence of extremes on a regional scale. It was evaluated for temperature and precipitation extremes for Poland. Daily homogenized data obtained from 14 weather stations, which cover most of the country, were used. The data used cover the 60-year period from 1951 to 2010. The index is based on relationships between extremes and mesoscale circulation conditions. The core material also included data describing circulation types for the study period. Three different calendars were used (Grosswetterlagen, by Lity?ski, by Nied?wied?). The conditional probability of the occurrence of extremes for particular types was calculated independently using partial indices (Partial Index of weather Extremes ? PIE). The higher the index values, the more favorable the synoptic situation for the occurrence of extremes. The results were grouped by describing the probability of temperature and precipitation extremes on the IPCC likelihood scale. Three thresholds corresponding to the frequency of an occurrence were identified via a seasonal approach. The CIE was validated using basic correlation coefficients as well as contingency tables based on feature-displacement criteria and Bayesian Probability Methods. The results confirmed the significance of atmospheric circulation in the formation of temperature and precipitation extremes in Poland. The CIE proved the relationship by trying to estimate the probability of temperature and precipitation extremes occurrence depending on the circulation type forecasted.